2015
DOI: 10.3389/fimmu.2015.00612
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Keys for Intestinal Barrier Modulation

Abstract: The intestinal tract represents the largest interface between the external environment and the human body. Nutrient uptake mostly happens in the intestinal tract, where the epithelial surface is constantly exposed to dietary antigens. Since inflammatory response toward these antigens may be deleterious for the host, a plethora of protective mechanisms take place to avoid or attenuate local damage. For instance, the intestinal barrier is able to elicit a dynamic response that either promotes or impairs luminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(180 citation statements)
references
References 176 publications
(222 reference statements)
5
151
0
8
Order By: Relevance
“…Female pups were not affected by LBN prior to weaning (Moussaoui, et al, 2016) although at weaning, the increase in permeability was observed in both sexes but to a greater extent in PND21 female pups. Diet and luminal factors (nutrients, bacteria, and bacterial products) can exert both beneficial and deleterious influences on the intestinal barrier (De Santis, Cavalcanti, Mastronardi, Jirillo, & Chieppa, 2015; Ulluwishewa et al, 2011; Winter, 2006). Food in the gut lumen is an important stimulus to mucosal cell growth.…”
Section: Metabolic Aspects Of the Lbn Paradigmmentioning
confidence: 99%
“…Female pups were not affected by LBN prior to weaning (Moussaoui, et al, 2016) although at weaning, the increase in permeability was observed in both sexes but to a greater extent in PND21 female pups. Diet and luminal factors (nutrients, bacteria, and bacterial products) can exert both beneficial and deleterious influences on the intestinal barrier (De Santis, Cavalcanti, Mastronardi, Jirillo, & Chieppa, 2015; Ulluwishewa et al, 2011; Winter, 2006). Food in the gut lumen is an important stimulus to mucosal cell growth.…”
Section: Metabolic Aspects Of the Lbn Paradigmmentioning
confidence: 99%
“…A recent review by De Santis et al detailed many dietary factors that may modulate the intestinal barrier (83). Here, we review some recent publications and emphasize the effects of diet-induced alterations of gut microbiota on compromising the gut barrier function.…”
Section: Mechanisms Of Leaky Gutmentioning
confidence: 99%
“…Akkermansia muciniphila is a mucin-degrading bacterium that resides in the mucus layer [15]. Recently some studies have demonstrated that A. muciniphila administration increased the intestinal levels of endocannabinoids that control inflammation, the gut barrier and gut peptide secretion [16]. Lactococcus lactis is a food-grade, Gram-positive lactic acid bacterium that is a harmless food industry bacterium, which has been used extensively for producing a variety of peptides, proteins, and oral vaccines.…”
Section: Discussionmentioning
confidence: 99%